Influence of tillage systems on yield and quality of durum wheat in Southern Italy - Pisante M.; Basso F. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
This paper presents an overview of research carried out in Southern Italy by various Italian researchers on the influence of different tillage systems on yield and quality of durum wheat. The effect of soil tillage treatments on grain yield and quality was described by means of selected data obtained through pluriennal research in the period 1976-1999. The comparisons were carried out in several localities in Southern Italy (Bari, Cerignola, Foggia, Guardia Perticara, Pietranera, Policoro and San Severo) on clay, clay-sandy and sand-silty soils. The compared soil tillage techniques were: Conventional Tillage (CT), Reduced Tillage (RT), Minimum Tillage (MT) and No Tillage (NT). The findings showed that the effects of the several tillage systems on durum wheat yield and quality change mainly in relation to the soil characteristics, but not in relation to the soil texture, and in particular circumstances to the soil moisture at tillage time and to the climatic course.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)